Move Still: The Effects of Implied and Real Motion on the Duration Estimates of Dance Steps. (July 2019) - Sgouramani, Helena; Moutoussis, Konstantinos; Vatakis, Argiro
It has been argued that movement can be implied by static cues of images depicting an instance of a dynamic event. Instances of implied motion have been investigated as a special type of stimulus with common processing mechanisms to those of real motion. Timing studies have reported a lengthening of the perceived time for moving as opposed to static stimuli and for stimuli of higher as compared to lower amounts of implied motion. However, the actual comparison of real versus implied motion on timing has never been investigated. In the present study, we compared directly the effect of two hypothetically analogous ballet steps with different amounts of movement and static instances of the dynamic peak of these events in a reproduction task. The analysis revealed an overestimation and lower response variability for real as compared to implied motion stimuli. These findings replicate and extend the apparent duration lengthening for moving as compared to static stimulation, even for static images containing implied motion, questioning whether or not the previously reported correspondence between real and implied motion transfers in the timing domain. This lack of correspondence was further supported by the finding that the amount of movement presented affected only displays of real motion.